2020
DOI: 10.1073/pnas.2004306117
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic sampling provides a unifying account of visual working memory limits

Abstract: Research into human working memory limits has been shaped by the competition between different formal models, with a central point of contention being whether internal representations are continuous or discrete. Here we describe a sampling approach derived from principles of neural coding as a framework to understand working memory limits. Reconceptualizing existing models in these terms reveals strong commonalities between seemingly opposing accounts, but also allows us to identify specific points of differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 67 publications
(90 reference statements)
7
87
0
Order By: Relevance
“…These tasks can be considered implicit in the sense that there is a nontrivial mapping from uncertainty to performance-maximizing behavior in a post-perceptual decision, but explicit in the sense that this decision is related to a conscious feeling of trust in a memory. Conversely, a whole-report experiment by Adam and others (2017) analyzed by Schneegans and others (2020) clearly demonstrates an implicit use of uncertainty by showing participants reported remembered items in decreasing order of memory precision. However, unlike in our study, this use was not behaviorally beneficial; Adam and colleagues found a nonsignificant performance difference when allowing participants to freely report versus being probed on which items to report their memory of.…”
Section: Discussionmentioning
confidence: 96%
“…These tasks can be considered implicit in the sense that there is a nontrivial mapping from uncertainty to performance-maximizing behavior in a post-perceptual decision, but explicit in the sense that this decision is related to a conscious feeling of trust in a memory. Conversely, a whole-report experiment by Adam and others (2017) analyzed by Schneegans and others (2020) clearly demonstrates an implicit use of uncertainty by showing participants reported remembered items in decreasing order of memory precision. However, unlike in our study, this use was not behaviorally beneficial; Adam and colleagues found a nonsignificant performance difference when allowing participants to freely report versus being probed on which items to report their memory of.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that the prioritized item was represented with enhanced fidelity in the pre-saccadic store. Both the decline in fidelity with set size ( Bays & Husain, 2008 ; Schneegans et al, 2020 ; van den Berg et al, 2012 ; Zhang & Luck, 2008 ) and the flexibility in allocation ( Gorgoraptis et al, 2011 ; Oberauer & Lin, 2017 ; Schmidt et al, 2002 ; Yoo et al, 2018 ) are characteristic qualities of visual working memory, often theorized to be the storage medium underlying transsaccadic integration (see Aagten-Murphy & Bays, 2019 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…One of the defining features of visual working memory is that the information it can hold is very limited ( Alvarez & Cavanagh, 2004 ; Cowan, 1998 ; Luck & Vogel, 1997 ). In analogue report tasks, this limit manifests as a decline in recall fidelity as the number of items in memory increases ( Ma, Husain, & Bays, 2014 ; Schneegans, Taylor, & Bays, 2020 ; van den Berg, Shin, Chou, George, & Ma, 2012 ; Zhang & Luck, 2008 ). Additionally, working memory allocation is flexible, so resources can be preferentially directed to particular items based on behavioral priority ( Bays, 2014 ; Bays & Husain, 2008 ; Oberauer & Lin, 2017 ; Schmidt, Vogel, Woodman, & Luck, 2002 ; Yoo, Klyszejko, Curtis, & Ma, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this is that time during retrieval is costly, and that rewards motivate people to pay that cost to maximise rewards. There are many forms this cost could take, for example in a recent WM model retrieval is proposed to occur via sampling spikes from neurons storing the items, and greater accuracy can be achieved at the cost of longer sampling times and more energy spent on generating spikes (Schneegans, Taylor, & Bays, 2020). Alternatively, time spent on one process is time not spent on another process, leading to opportunity costs for every cognitive function, which are balanced depending on the values associated with their outcomes (Kurzban, Duckworth, Kable, & Myers, 2013;Shenhav et al, 2017).…”
Section: Discussionmentioning
confidence: 99%